Mathematics Anxiety Among Primary School Teachers: Scale Adaptation and Anxiety Level Determination Study - Bozkurt, Eyüp; Deniz, Kılıç (My University, 2025)
Purpose: This study aims to adapt a scale to measure the mathematics anxiety of primary school teachers and to determine their anxiety levels. Mathematics anxiety can significantly impact teachers' professional competencies and their effects on students. Therefore, accurately determining teachers' anxiety levels and developing strategies to reduce this anxiety is of great importance. Design/Methodology/Approach: The research used a cross-sectional survey design and was carried out with 300 primary school teachers from various regions across Turkey during the spring term of 2023. Data were collected through an online survey, and validity and reliability analyses were conducted on the adapted scale. Expert opinions were sought for the linguistic and cultural adaptation of the scale, a pilot study was conducted, and then the main study was carried out. Findings: The findings obtained during the scale adaptation process indicate that the scale is valid and reliable. The mathematics anxiety levels of teachers show significant differences according to variables such as gender, age, and professional experience. Notably, it was found that female teachers have higher levels of mathematics anxiety compared to male teachers. Additionally, teachers with less professional experience were found to have higher anxiety levels. Highlights: Mathematics anxiety among primary school teachers is a crucial factor that should be considered when developing educational policies and teacher training programs. Strategies and support programs to reduce mathematics anxiety are recommended. Teacher training programs should include methods and techniques to reduce mathematics anxiety.
Keywords: Scale adaptation; Primary school teachers; Mathematics anxiety; Anxiety level